Untargeted metabolomics of saliva in pregnant women with and without gestational diabetes mellitus and healthy non-pregnant women - Li, Yueheng; Feng, Yang; Yang, Zhengyan; Zhou, Zhi; Jiang, Dan; Luo, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The aim of this study was to compare the differences in salivary metabolites between pregnant women with gestational diabetes mellitus (GDM), healthy pregnant women (HPW), and healthy non-pregnant women (HNPW), and analyze the possible associations between the identified metabolites and gingivitis. Method The study included women with GDM (n = 9, mean age 28.9 ± 3.6 years, mean gestational age 30.1 ± 3.2 weeks), HPW (n = 9, mean age 27.9 ± 3.0 years, mean gestational age 28.6 ± 4.7 weeks), and HNPW (n = 9, mean age 27.7 ± 2.1 years). Saliva samples were collected from all participants and were analyzed with LC-MS/MS-based untargeted metabolomic analysis. Metabolite extraction, qualitative and semi-quantitative analysis, and bioinformatics analysis were performed to identify the differential metabolites and metabolic pathways between groups. The identified differential metabolites were further analyzed in an attempt to explore their possible associations with periodontal health and provide evidence for the prevention and treatment of periodontal inflammation during pregnancy. Results In positive ion mode, a total of 2,529 molecular features were detected in all samples, 166 differential metabolites were identified between the GDM and HPW groups (89 upregulated and 77 downregulated), 823 differential metabolites were identified between the GDM and HNPW groups (402 upregulated and 421 downregulated), and 647 differential metabolites were identified between the HPW and HNPW groups (351 upregulated and 296 downregulated). In negative ion mode, 983 metabolites were detected in all samples, 49 differential metabolites were identified between the GDM and HPW groups (29 upregulated and 20 downregulated), 341 differential metabolites were identified between the GDM and HNPW groups (167 upregulated and 174 downregulated), and 245 differential metabolites were identified between the HPW and HNPW groups (112 upregulated and 133 downregulated). A total of nine differential metabolites with high confidence levels were identified in both the positive and negative ion modes, namely, L-isoleucine, D-glucose 6-phosphate, docosahexaenoic acid, arachidonic acid, adenosine, adenosine-monophosphate, adenosine 5′-monophosphate, xanthine, and hypoxanthine. Among all pathways enriched by the upregulated differential metabolites, the largest number of pathways were enriched by four differential metabolites, adenosine, adenosine 5′-monophosphate, D-glucose 6-phosphate, and adenosine-monophosphate, and among all pathways enriched by the downregulated differential metabolites, the largest number of pathways were enriched by three differential metabolites, L-isoleucine, xanthine, and arachidonic acid. Conclusion Untargeted metabolomic analysis of saliva samples from pregnant women with GDM, HPW, and HNPW identified nine differential metabolites with high confidence. The results are similar to findings from previous metabolomics studies of serum and urine samples, which offer the possibility of using saliva for regular noninvasive testing in the population of pregnant women with and without GDM. Meanwhile, the associations between these identified differential metabolites and gingivitis need to be further validated by subsequent studies.